Study of SPWM and HCF control schemes of UPFC - Zhang, Wei (2008)
In recent years, high-speed control of power flow over AC transmission system is available with the evolution of Flexible AC Transmission System (FACTS). The latest FACTS device, Unified Power Flow Controller (UPFC), connects the Static Synchronous Compensator (STATCOM) and Static Synchronous Series Compensator (SSSC) together with a DC capacitor and combines their advantages and functions. It has been accepted to be the most powerful FACTS controller and selected to be the central direction of the research work.